LEARNERS’ PERCEPTION AND PRACTICES ON AUTONOMOUS LANGUAGE LEARNING IN EFL SETTINGS - Marsevani, Maya (Universitas Pendidikan Ganesha, 2021)
This research was aimed to investigate learners’ perception and practices of understanding teachers’ teaching objectives and requirements related to autonomous language learning, setting up their objectives and study plans to autonomous language learning, and find out learners perceive in learning English autonomously. To gain a deep understanding and utilizing the objectives, the researcher employed descriptive qualitative research. The research findings were extracted through both an online questionnaire and interview. Some constraints were reported in this research, but more positive responses were still shown by the learners. They positively disposed to the notion of learner autonomy. The learners specifically showed positive attitudes toward instructors’ teaching objectives and requirements, setting up their objectives and study plans, and their practices in learning English autonomously. Further researchers, thus, need to research in various universities with a large number to gain a deeper and wider understanding about learners perceive in autonomous language learning.